Răspuns :
Răspuns:
Explicație pas cu pas:
( 3 × 9 + 7 × h - 53 ) + 5 × 2 - ( 12 - 4 × 2 ) = 6 × 6
( 27 + 7 × h - 53 ) + 10 - ( 12 - 8 ) = 36
( 27 + 7 × h - 53 ) + 10 - 4 = 36
27 + 7 × h - 53 = 36 + 4 - 10 → aplic metoda mersului invers
27 + 7 × h - 53 = 40 - 10
27 + 7 × h - 53 = 30
27 + 7 × h = 30 + 53
7 × h = 83 - 27
7 × h = 56
h = 56 : 7
h = 8
(3*9+7*h-53)+5*2-(12-4*2)=6*6
[tex]\it (3\cdot9+7\cdot h-53)+5\cdot2-(12-4\cdot2)=6\cdot6 \Rightarrow (27+7h-53)+10-4=36 \Rightarrow\\ \\ \Rightarrow (7h-26)+6=36|_{-6} \Rightarrow7h-26=30 |_{+26} \Rightarrow7h=56|:7 \Rightarrow h=8[/tex]